Meta‐analysis of laparoscopic versus open cholecystectomy for patients with liver cirrhosis and symptomatic cholecystolithiasis. Issue 2 (3rd October 2012) - de Goede, B.; Klitsie, P. J.; Hagen, S. M.; van Kempen, B. J. H.; Spronk, S.; Metselaar, H. J.; Lange, J. F.; Kazemier, G.
Abstract Background: Open cholecystectomy (OC) is often preferred over laparoscopic cholecystectomy (LC) in patients with liver cirrhosis and portal hypertension, but evidence is lacking to support this practice. This meta‐analysis aimed to clarify which surgical technique is preferable for symptomatic cholecystolithiasis in patients with liver cirrhosis. Methods: A meta‐analysis was conducted according to the PRISMA guidelines. Articles published between January 1990 and October 2011 were identified from MEDLINE, Embase and the Cochrane Library. Randomized clinical trials (RCTs) comparing outcomes of OC versus LC for cholecystolithiasis in patients with liver cirrhosis were included. The quality of the RCTs was assessed using the Jadad criteria. Results: Following review of 1422 papers by title and abstract, a meta‐analysis was conducted of four RCTs comprising 234 surgical patients. They provided evidence of at least level 2b on the Oxford Level of Evidence Scale, but scored poorly according to the Jadad criteria. Some 97·0 per cent of the patients had Child–Turcotte–Pugh (CTP) grade A or B liver cirrhosis. In all, 96·6 per cent underwent elective surgery. No postoperative deaths were reported. LC was associated with fewer postoperative complications (risk ratio 0·52, 95 per cent confidence interval (c.i.) 0·29 to 0·92; P = 0·03), a shorter hospital stay (mean difference − 3·05 (95 per cent c.i. − 4·09 to − 2·01) days; P < 0·001) and quicker resumption of a normal diet (mean difference − 27·48 (−30·96 to − 23·99) h; P < 0·001). Conclusion: Patients with CTP grade A or B liver cirrhosis who undergo LC for symptomatic cholecystolithiasis have fewer overall postoperative complications, a shorter hospital stay and resume a normal diet more quickly than those who undergo OC. Copyright © 2012 British Journal of Surgery Society Ltd. Published by John Wiley & Sons, Ltd.